Karta Zaliva Cv. Lavrentiia i smezhnykh zemel k istoriu o stranst’iiakh voobshche - Bellin, Jacques Nicolas, 1703-1772 (1757)
Black and white. Prime meridian Paris. Decorative title cartouche. Bar scale.